Vinylidene fluoride polymer dispersion
By emulsifying polymerization in water, using carbon chloride chain transfer agent and inorganic starting agent, high molecular weight VDF polymer dispersions are prepared, which solves the problem of insoluble residues of high molecular weight VDF polymer dispersions in the prior art, and achieves efficient preparation and excellent application performance.
Patent Information
- Application Number
- JP2021535719
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-20
- Filing Date
- 2019-12-02
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2039-12-02
AI Technical Summary
It is difficult to produce high molecular weight aqueous polyvinyl fluoride (VDF) polymer dispersions, and these dispersions are often accompanied by insoluble residues at high molecular weight, affecting their application in battery modules and membrane production.
By performing emulsification polymerization in water, using carbon chloride chain transfer agent and inorganic starting agent, the iodine content and chain end composition in the polymerization reaction are controlled, and a high molecular weight VDF polymer dispersion is prepared to ensure its linear structure and low insoluble residue.
The efficient preparation of high molecular weight VDF polymer dispersion is achieved, the content of insoluble residues is reduced, and its application performance in battery modules and membrane production is improved.
Smart Images

Figure 0007657716000017 
Figure 0007657716000001 
Figure 0007657716000002
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to European Patent Application No. 18214303.2, filed December 20, 2018, the entire contents of which are incorporated herein by reference for all purposes.
[0002] The present invention relates to aqueous vinylidene fluoride polymer dispersions, to a process for their preparation and to their use for producing electrochemical cell components, such as electrodes and / or composite separators, or for producing membranes, in particular porous membranes. [Background technology]
[0003] It is known in the art that vinylidene fluoride (VDF) polymers are suitable as binders for the manufacture of electrodes, particularly cathodes, composite separators and / or for the coating of porous separators for use in non-aqueous electrochemical devices such as batteries, preferably secondary batteries and electric double layer capacitors. More generally, VDF polymers find utility in various other fields of use, including in particular architectural coatings, membrane production, coatings for the chemical industry and / or O&G applications, as their durability, chemical inertness and other advantageous properties are highly valuable.
[0004] The main materials available on the market for this field of use are VDF polymers produced by suspension polymerization, which can be modified by the incorporation of polar groups and are generally processed by dissolution in a solvent system comprising N-methylpyrrolidone or a mixture of N-methylpyrrolidone with diluent solvents such as acetone, propyl acetate, methyl ethyl ketone and ethyl acetate. A typical material is disclosed in EP 2147029(A) (SOLVAY SOLEXIS SPA), filed on 27 January 2010, which provides a linear semi-crystalline copolymer comprising repeat units derived from vinylidene fluoride (VDF) monomers and at least one hydrophilic (meth)acrylic monomer, which has improved thermal stability and also provides excellent adhesion when used as a binder in batteries.
[0005] Although suspension-based VDF polymer based technologies have been pursued, there is growing interest in emulsion polymerized VDF polymer dispersions, driven by both economic and environmental considerations.
[0006] It is in fact generally recognized that the post-processing of emulsion polymerized VDF polymers results in fine powders with a larger surface area than suspension polymerized VDF polymers, which leads to easier dissolution and therefore faster processing in all the solvent-based processing techniques that are often used.Furthermore, aqueous dispersions are advantageous in all those areas where non-solvent based solutions are required.
[0007] Moreover, in the field of VDF polymer powders, it is generally recognized that a high molecular weight is beneficial for this field of use. Notably, European Patent Application No. 0791973(A) (KUREHA), filed on August 27, 1997, relates to a binder liquid for providing an electrode suitable for use in non-aqueous electrochemical devices, such as batteries and electrode double layer capacitors, which is formed by dissolving a vinylidene fluoride polymer having a higher intrinsic viscosity (and therefore degree of polymerization) than conventional levels in an organic solvent. An electrode-forming composition is formed by dispersing a powdered electrode material in the binder liquid, which is applied onto a conductive substrate and then dried to form a composite electrode layer that holds the powdered electrode material with a lower amount of vinylidene fluoride polymer material than conventional levels and has good resistance to non-aqueous electrolyte solutions.
[0008] Nevertheless, it is generally recognized that higher polymerization temperatures, lower pressures and other polymerization parameters of emulsion polymerization result in a higher number of inversions (head-to-head / tail-to-tail) / branches / defects with respect to the theoretical linear sequence of head-to-tail repeating units, and all these phenomena become worse when aiming at higher molecular weights. As a result, high molecular weight VDF polymers from emulsion polymerization are generally accompanied by a significant gel fraction or insoluble residue fraction and peculiar rheological behavior due to the presence of long chain branches.
[0009] Therefore, in order to effectively utilize emulsion polymerized VDF polymers in electrode or separator formation processes, as well as in various other fields of use involving processing in solution, such as porous membrane production, it is important to utilize materials that are endowed with higher molecular weights but that are essentially free of gel / insoluble fractions.
[0010] There is therefore a continuing need in this field for aqueous dispersions of high molecular weight VDF polymers which have all the properties required for use in the field of components for secondary batteries and more generally are suitable for processing from solution, but which are essentially free of gel / insoluble fractions.
[0011] Currently, there is known a technique for preparing VDF dispersions based on aqueous emulsion polymerization, generally in the presence of fluorinated emulsifiers.Furthermore, the use of iodine-containing chain transfer agents in the emulsion polymerization of VDF to provide thermoplastic VDF polymers has already been described in general terms in the art.A significant disclosure of this is provided in US Patent No. 4,158,678 (DAIKIN) 19 / 06 / 1979, but this technique is intended to produce iodine endblocks, which have reactive chain ends to produce block copolymers in a further polymerization step. Summary of the Invention
[0012] The Applicant has now discovered that a solution to the problem defined above is an aqueous dispersion [dispersion (D)] comprising particles of a vinylidene fluoride (VDF) polymer [polymer (A)] comprising repeat units derived from a vinylidene fluoride (VDF) monomer, said polymer (A) being (i) Contains more than 85.0 mol % of repeat units derived from VDF, based on the total number of repeat units of polymer (A); (ii) having an iodine-containing chain end in an amount of 0.1 to 10.0 mmol / kg; (iii) a weight average molecular weight (M) of at least 500 kilodaltons, as measured by gel permeation chromatography (GPC) using N,N-dimethylacetamide (DMA) as the solvent, relative to monodisperse polystyrene standards; w ) According to ASTM D3835, 100 sec -1 The melt viscosity (MV) in kilopoises and M in kilodaltons are determined at a shear rate of 1000 MPa and a temperature of 230°C. w The relationship between is the following inequality: 0.025×M w (kilodalton) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodaltons)+10 It has been found that the above-mentioned property is provided by an aqueous dispersion [dispersion (D)] which satisfies the above-mentioned requirements.
[0013] The present invention further relates to a process for the preparation of said dispersion (D), comprising the emulsion polymerization of VDF in an aqueous medium in the presence of an inorganic initiator and an iodine-containing chain transfer agent, the molar ratio between the iodine-containing chain transfer agent and the initiator being less than 0.100 mol / mol.
[0014] Yet another object of the present invention is a powder comprising particles of a vinylidene fluoride (VDF) polymer [polymer (A)] comprising repeat units derived from a vinylidene fluoride (VDF) monomer, said polymer (A) being (i) Contains more than 85.0 mol % of repeat units derived from VDF, based on the total number of repeat units of polymer (A); (ii) having an iodine-containing chain end in an amount of 0.1 to 5 mmol / kg; (iii) a weight average molecular weight (M) of at least 500 kilodaltons, as measured by gel permeation chromatography (GPC) using N,N-dimethylacetamide (DMA) as the solvent, relative to monodisperse polystyrene standards; w ) According to ASTM D3835, 100 sec -1 The melt viscosity (MV) in kilopoises and M in kilodaltons are determined at a shear rate of 1000 MPa and a temperature of 230°C. w The relationship between is the following inequality: 0.025×M w (kilodalton) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodaltons)+10 and said particles of polymer (A) have an average primary particle size of less than 1 μm.
[0015] The Applicant has surprisingly found that this manufacturing method makes it possible to produce dispersions of VDF polymers, so that the insoluble fraction / gels due to long branched / crosslinked polymer chains are substantially reduced, while still having a quasi-linear structure, as expressed by the above specific relationship between MV and Mw, and while achieving a high molecular weight of the VDF polymers contained therein, so as to result in very good behavior in the field of use of electrochemical cell components.
[0016] Furthermore, the method of the present invention provides VDF polymers that are particularly suitable for being processed from solution due to their total solubility behavior, whereby due to their substantially linear microstructure, even at high molecular weights, solutions with reasonable liquid viscosities are obtained. Such VDF polymers are also useful for the manufacture of membranes, especially porous membranes. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a graph showing the relationship between melt viscosity in kilopoise (MV) and weight average molecular weight in kilodaltons (Mw) measured for a VDF polymer of the invention (□), a reference emulsion-polymerized VDF-polymer (●) and a reference suspension-polymerized polymer (○). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Polymer (A) contains repeat units derived from vinylidene fluoride (VDF).
[0019] The polymer (A) may further comprise repeat units derived from at least one other comonomer (C) different from VDF.
[0020] The comonomer (C) can be either a hydrogenated comonomer [comonomer (H)] or a fluorinated comonomer [comonomer (F)].
[0021] The term "hydrogenated comonomer [comonomer (H)]" is intended in this specification to mean an ethylenically unsaturated comonomer that does not contain a fluorine atom.
[0022] Non-limiting examples of suitable hydrogenated comonomers (H) include, inter alia, vinyl monomers such as ethylene, propylene, vinyl acetate, and styrenic monomers such as styrene and p-methylstyrene.
[0023] Monomer (H) may be a monomer containing at least one polar group selected from the group consisting of a hydroxyl group, a carboxylic acid group, and an epoxy group.
[0024] According to a particularly preferred embodiment, the polymer (A) has the following formula: TIFF0007657716000001.tif26170 (wherein R1, R2, and R3 are equal to or different from each other and independently represent a hydrogen atom or a C1 to C3 hydrocarbon group; R OH is a hydroxyl group or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group).
[0025] The term "fluorinated comonomer [comonomer (F)]" is intended herein to mean an ethylenically unsaturated comonomer which contains at least one fluorine atom.
[0026] The comonomer (C) is preferably a fluorinated comonomer [comonomer (F)].
[0027] Non-limiting examples of suitable fluorinated comonomers (F) include, in particular: (a) C2 to C8 fluoro- and / or perfluoroolefins, such as tetrafluoroethylene (TFE), hexafluoropropylene (HFP), pentafluoropropylene, and hexafluoroisobutylene; (b) C2-C8 hydrogenated monofluoroolefins, such as vinyl fluoride, 1,2-difluoroethylene, and trifluoroethylene; (c)Formula CH2=CH-R f0 (In the formula, R f0 is a C1-C6 perfluoroalkyl group), (d) chloro-, and / or bromo-, and / or iodo-C2-C6 fluoroolefins, such as chlorotrifluoroethylene (CTFE); (e) Formula CF2=CFOR f1 (In the formula, R f1 is a C1-C6 fluoro- or perfluoroalkyl group, for example -CF3, -C2F5, -C3F7), (per)fluoroalkyl vinyl ethers, (f) Formula CF2=CFOX0 (wherein X0 is a C1-C 12 Oxyalkyl group or C1-C 12 (per)fluoro-oxyalkyl vinyl ethers of (per)fluorooxyalkyl groups, for example the perfluoro-2-propoxy-propyl group; (g)Formula CF2=CFOCF2OR f2 (In the formula, R f2 is a C1-C6 fluoro- or perfluoroalkyl group, for example -CF3, -C2F5, -C3F7, or a C1-C6 (per)fluorooxyalkyl group having one or more ether groups, for example -C2F5-O-CF3), Formula (h): TIFF0007657716000002.tif39170 (in the formula, R f3、 R f4、 R f5 , and R f6 each of which is equal to or different from one another and is independently a C1-C6 fluoro- or per(halo)fluoroalkyl group containing a fluorine atom, optionally one or more oxygen atoms, e.g., -CF3, -C2F5, -C3F7, -OCF3, -OCF2CF2OCF3) fluorodioxole.
[0028] The most preferred fluorinated comonomers (F) are tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorotrifluoroethylene (CTFE), hexafluoropropylene (HFP), perfluoromethyl vinyl ether (PMVE), perfluoropropyl vinyl ether (PPVE) and vinyl fluorides, of which HFP is the most preferred.
[0029] When at least one comonomer (C), preferably HFP, is present, polymer (A) typically comprises from 0.05 mol % to 14.5 mol %, preferably from 1.0 mol % to 13.0 mol %, of repeat units derived from said comonomer (C) relative to the total moles of repeat units of polymer (A).
[0030] However, the amount of repeating units derived from vinylidene fluoride in polymer (A) must be at least 85.0 mol%, preferably at least 86.0 mol%, more preferably at least 87.0 mol%, so as not to impair the excellent properties of vinylidene fluoride resin, such as chemical resistance, weather resistance, and heat resistance. For example, if polymer (A) contains VDF units in an amount less than 85.0 mol%, the corresponding polymer will dissolve in a liquid solvent used as an electrode liquid phase, and therefore polymer (A) cannot be used to prepare a coating composition for producing a composite separator for a battery.
[0031] The term "at least one hydrophilic (meth)acrylic monomer (MA)" is understood to mean that the polymer (A) may contain repeat units derived from one or more hydrophilic (meth)acrylic monomers (MA) as defined above. In the remainder of the specification, the expressions "hydrophilic (meth)acrylic monomer (MA)" and "monomer (MA)" are understood for the purposes of the present invention to refer both to the plural and to the singular, i.e. to one or more of both hydrophilic (meth)acrylic monomers (MA).
[0032] According to a particular embodiment, the polymer (A) consists essentially of repeat units derived from VDF and monomer (MA).
[0033] According to another embodiment, polymer (A) consists essentially of repeat units derived from VDF, HFP and monomer (MA).
[0034] The expression "consisting essentially of," when used in connection with the repeat units of polymer (A), is understood to mean that in addition to the listed repeat units, defects, end chains and impurities may be present in polymer (A) without substantially affecting the advantageous characteristics of polymer (A).
[0035] Polymer (A) may also contain other moieties, such as defects, end groups, etc., which do not affect or impair its physical-chemical properties, provided that the inequality between weight average molecular weight and melt viscosity described above is satisfied.
[0036] The hydrophilic (meth)acrylic monomer (MA) preferably has the formula: TIFF0007657716000003.tif28170 (in the formula, R1, R2, R OH each of R1, R2, R3 has the meaning defined above, and R3 is hydrogen, more preferably each of R1, R2, R3 is hydrogen, while R OH have the same meaning as set out above).
[0037] Non-limiting examples of hydrophilic (meth)acrylic monomers (MA) are in particular acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate; hydroxyethylhexyl (meth)acrylate.
[0038] The monomer (MA) is more preferably - Formula: Hydroxyethyl acrylate (HEA) from TIFF0007657716000004.tif25170, - The following formula: TIFF0007657716000005.tif32170 2-Hydroxypropyl acrylate (HPA) - Formula: TIFF0007657716000006.tif27170 Acrylic Acid (AA) - and mixtures thereof is selected from.
[0039] More preferably, the monomer (MA) is AA and / or HEA, even more preferably AA.
[0040] The determination of the amount of (MA) monomer repeat units in polymer (A) can be carried out by any suitable method, including, inter alia, acid-base titration (well suited for example to determine the acrylic acid content), NMR methods (suitable for the quantification of (MA) monomers containing aliphatic hydrogens in the side chain (e.g. HPA, HEA)), weight balance based on the total (MA) monomers fed during the preparation of polymer (A) and on the unreacted residual (MA) monomers.
[0041] Preferably, polymer (A) comprises at least 0.1 mol %, more preferably at least 0.2 mol %, of repeat units derived from said hydrophilic (meth)acrylic monomers (MA) and / or polymer (A) comprises preferably at most 10 mol %, more preferably at most 7.5 mol %, even more preferably at most 5 mol %, most preferably at most 3 mol % of repeat units derived from said hydrophilic (meth)acrylic monomers (MA).
[0042] The polymer (A) has a weight average molecular weight (M) of at least 500 kilodaltons as measured by gel permeation chromatography (GPC) using N,N-dimethylacetamide (DMA) as the solvent against monodisperse polystyrene standards. w ) M wThe upper limit is not particularly critical, but it is nevertheless understood that polymer (A) will generally have a Mw of at most 1500 kilodaltons, preferably at most 1400 kilodaltons, and even more preferably at most 1300 kilodaltons.
[0043] M w Particularly preferred is a polymer (A) having a molecular weight of at least 550 kilodaltons, even more preferably at least 600 kilodaltons and / or a molecular weight of at most 1250 kilodaltons, even more preferably at least 1200 kilodaltons.
[0044] As described above, the polymer (A) satisfies the following inequality: 0.025×M w (kilodalton) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodaltons)+10 Meets ASTM D3835 100sec -1 The melt viscosity (MV) in kilopoise and M in kilodaltons are determined at a shear rate of 1000 and a temperature of 230°C. w It is characterized by the relationship:
[0045] Applicants are not bound by this theory, w Considering that at a given value of , the polymer (A) of the aqueous dispersion of the present invention is characterized by a lower melt viscosity than the conventional emulsion-polymerized VDF polymers, the viscosity being strongly influenced by the entanglements between short and long chain branches and therefore approaching the melt viscosity of the suspension-polymerized VDF polymers known for their more linear and regular structure.
[0046] Preferably, MV satisfies the inequality: MV (kilopoise)>0.030×M w (kilodaltons) + 12 and / or MV (kilopoise) ≤ 0.045 x M w Meets (kilodaltons) +9.
[0047] Most preferably, the MV satisfies the inequality: 0.030×M w(kilodalton) + 12 ≤ MV (kilopoise) ≤ 0.045 x M w Meets (kilodaltons) +9.
[0048] By melt viscosity per se, polymer (A) is generally understood to have a melt viscosity, measured under the above conditions, of generally at least 23.5, preferably at least 27.0, more preferably at least 28.0 kpoise, and / or generally at most 58.0, preferably at most 57.0 kpoise.
[0049] According to a particular embodiment, the polymer (A) has an MV of at least 35.0, preferably at least 36.0 kpoise, and / or at most 52.0, preferably at most 50.0 kpoise, which MV will be adequate to ensure optimal properties in electrochemical applications.
[0050] Generally, the particles of polymer (A) have a primary particle average diameter of less than 1 μm. For the purposes of the present invention, the term "primary particles" is intended to mean the primary particles of polymer (A) derived directly from aqueous emulsion polymerization, without isolating the polymer from the emulsion (i.e., latex). Thus, the primary particles of polymer (A) are intended to be distinguishable from the agglomerates (i.e., collections of primary particles) that may be obtained by the recovery and conditioning steps of such polymer production, such as concentrating and / or coagulating the aqueous latex of polymer (A) and then drying and homogenizing to produce the respective powders.
[0051] The dispersion (D) of the present invention can therefore be distinguished from an aqueous slurry which can be prepared by dispersing a powder of a polymer in an aqueous medium. The average particle size of the powder of the polymer or copolymer dispersed in the aqueous slurry is usually greater than 1 μm, as measured according to ISO 13321.
[0052] Preferably, the particles of polymer (A) in dispersion (D) have a mean primary particle size, measured according to ISO 13321, of more than 20 nm, more preferably more than 30 nm, even more preferably more than 50 nm, and / or less than 600 nm, more preferably less than 400 nm, even more preferably less than 350 nm.
[0053] As noted above, polymer (A) is required to contain iodine-containing chain ends.
[0054] Polymer (A) preferably has iodine-containing chain ends in an amount of at least 0.5, preferably at least 1.0 mmol / kg and / or at most 7.5, preferably at most 6.0 mmol / kg, most preferably 5.0 mmol / kg.
[0055] In fact, said amount of iodine-containing chain ends is an unavoidable feature due to the use of iodine-containing chain transfer agents in the emulsion polymerization for the preparation of the dispersion (D). Nevertheless, said carefully adapted amount represents the use of the minimum necessary amount of chain agent in order to ensure a quasi-living feature for the polymerization chain growth without having competing chain transfers for the chain growth, thus ultimately limiting the achievable molecular weight and / or imparting chemical reactivity / instability to the final polymer (A) due to the presence of said chain ends.
[0056] Generally, the chain end is of the formula -CH2I.
[0057] The concentration of chain ends can be determined by elemental analysis; if the polymer (A) contains iodine-containing end groups of formula -CH2-I, their amount can be determined according to the technique detailed in PIANCA, M. et al., End groups in fluoropolymers. Journal of Fluorine Chemistry. 1999, vol. 95, p. 71-84. 1 It can be determined by H-NMR. In a manner substantially similar per se, the -CF2-CH2Br or -CF2-CH2OH end groups are determined taking into account the chemical shift of -CH2I.
[0058] According to a particularly preferred embodiment, the dispersion (D) is substantially free of fluorinated surfactants.
[0059] The expression "substantially free" in combination with the amount of fluorinated surfactant in dispersion (D) should be interpreted as excluding the presence of any significant amount of said fluorinated surfactant, for example requiring that the fluorinated surfactant be present in an amount of less than 5 ppm, preferably less than 3 ppm, more preferably less than 1 ppm relative to the total weight of dispersion (D).
[0060] When the dispersion (D) is substantially free of fluorinated surfactants, the presence of a certain number of polar end groups of the polymer (A) is generally required in the dispersion (D) to ensure adequate colloidal stability. According to these embodiments, the polymer (A) is, according to PIANCA, Maurizio et al., End Groups in fluoropolymers. Journal of Fluorine Chemistry. 1999, vol. 95, p. 71-84, 1 It is generally required to contain an amount of polar end groups of the formula -CH2-OH of at least 5.0 mmol / kg as determined by H-NMR.
[0061] Preferably, in these preferred embodiments, the polymer (A) comprises an amount of polar end groups of formula -CH2-OH of at least 5.5 mmol / kg, preferably at least 6.0 mmol / kg, and / or advantageously at most 15.0 mmol / kg, preferably at most 14.0 mmol / kg, even more preferably at most 13.0 mmol / kg.
[0062] Very good results have been obtained when polymer (A) contains an amount of polar end groups of formula -CH2-OH of at least 7.0 mmol / kg and at most 10.0 mmol / kg.
[0063] Additionally, polymer (A) may contain, in addition to the iodine-containing chain ends and polar end groups of formula -CH-OH, non-polar end groups, including any group of formula -CFH and -CFCH, which may be viewed as additional chain ends for interchain termination and / or for backbiting intrachain migration.
[0064] Due to controlled pseudo-living polymerization, in polymer (A), the total amount of any end groups of formula -CF2H and -CF2CH3 in polymer (A) is advantageously 60.0mmol / kg or less, preferably 55.0mmol / kg or less, more preferably 50.0mmol / kg or less. The lower limit for the total amount of end groups of formula -CF2H and -CF2CH3 is not particularly limited. Nevertheless, it is understood that in general, an amount of at least 1.0mmol / kg, preferably at least 1.5mmol / kg, more preferably at least 2.0mmol / kg even remains unavoidable and is not considered to adversely affect the performance of dispersion (D) and polymer (A).
[0065] The present invention further relates to a process for the preparation of a dispersion (D) comprising particles of polymer (A) as detailed above, comprising the emulsion polymerization of VDF in the presence of an inorganic initiator and an iodine-containing chain transfer agent, the molar ratio between said iodine-containing chain transfer agent and said initiator being less than 0.100 mol / mol.
[0066] The method of the present invention is typically carried out in the presence of at least one radical initiator.Generally, for the embodiment in which no fluorosurfactant is added, inorganic radical initiators are preferred due to their ability to generate polar chain ends, which have a stabilizing effect on the particles of polymer (A) in dispersion (D).Persulfate radical initiators are generally the ones most used for this purpose.
[0067] The selection of the persulfate radical initiator is not particularly limited, but it is understood that suitable radical initiators for the aqueous emulsion polymerization process are selected from compounds capable of initiating and / or accelerating the polymerization process, including, but not limited to, sodium persulfate, potassium persulfate, and ammonium persulfate.
[0068] One or more radical initiators as defined above may be added to the aqueous medium defined above in an amount advantageously ranging from 0.001% to 20% by weight, based on the weight of the aqueous medium.
[0069] As mentioned above, in the process of the present invention, an iodine-containing chain transfer agent is added. The iodine-containing chain transfer agent is generally selected from the group consisting of: - Formula R H (I) x (In the formula, R H is a fluorine-free alkyl group containing 1 to 8 carbon atoms and x is an integer from 0 to 2; one example of which is CH2I2; - Formula R f (I) x (In the formula, R f is a (per)fluoroalkyl or (per)fluorochloroalkyl containing 1 to 8 carbon atoms, and x is an integer from 0 to 2; one example of which is diiodoperfluorobutane, of formula C4F8I2; and - alkali metal or alkaline earth metal iodides, such as in particular those described in US Patent No. 5,173,553 (AUSIMONT SRL) of Dec. 22, 1992. Potassium iodide has been found to be particularly effective as an iodine chain transfer agent in the process of the invention.
[0070] As explained above, the molar ratio between the iodine-containing chain transfer agent and the initiator is less than 0.100 mol / mol.The applicant has surprisingly found that such a low amount of iodine-containing chain transfer agent is effective in promoting the pseudo-living feature of polymerization, while making it possible to achieve high molecular weight and avoid any modification in the performance of the final polymer (A).The amount is preferably such that the molar ratio between the iodine-containing chain transfer agent and the initiator is at most 0.075, more preferably at most 0.065 mol / mol, and even more preferably at most 0.060 mol / mol.
[0071] The lower limit of the iodine-containing chain transfer agent is not particularly limited, but an amount is generally used to provide a molar ratio between the iodine-containing chain transfer agent and the initiator of at least 0.005, preferably at least 0.015, more preferably at least 0.020 mol / mol.
[0072] As mentioned above, the present method preferably comprises the step of reacting a compound of the formula (III) below: R f§ (X - ) k (M + ) k (III) (In the formula, -R f§ C5-C, optionally containing one or more catenary or non-catenary oxygen atoms 16 selected from (per)fluoroalkyl chains and (per)fluoropolyoxyalkyl chains; -X - -COO - , -PO3 - and -SO3 - is selected from -M + is NH4 + and an alkali metal ion, -k is 1 or 2) without the addition of a corresponding fluorinated surfactant (FS).
[0073] Non-limiting examples of fluorinated surfactants (FS) whose presence is substantially avoided in the dispersion (D) are: (a) CF3 (CF2) n0 COOM', where n0 is an integer ranging from 4 to 10, preferably from 5 to 7, preferably n1 is equal to 6, and M' represents NH4, Na, Li or K, preferably NH4; (b) T-(C3F6O) n1 (CFXO) m1 CF2COOM″ (where T is a Cl atom or x F 2x+1-x’ Cl x’ O perfluoroalkoxide group (wherein x is an integer ranging from 1 to 3, x' is 0 or 1), n1 is an integer ranging from 1 to 6, m1 is an integer ranging from 0 to 6, M'' represents NH4, Na, Li, or K, and X represents F or -CF3); (c)F-(CF2CF2) n2 -CH2-CH2-RO3M''', where R is a phosphorus or sulfur atom, preferably R is a sulfur atom, M''' represents NH4, Na, Li or K, and n2 is an integer ranging from 2 to 5, preferably n2 is equal to 3; (d)AR bf -B bifunctional fluorinated surfactant, where A and B are equal to or different from each other and have the formula -(O) p CFX''-COOM * (In the formula, M * represents NH4, Na, Li or K, preferably M * represents NH4, X″ is F or —CF3, and p is an integer equal to 0 or 1, bf AR bf - B is a divalent (per)fluoroalkyl or (per)fluoropolyether chain such that the number average molecular weight of B is in the range of 300 to 1800; and (e) Mixtures thereof.
[0074] Yet another object of the present invention is a powder [powder (P)] comprising particles of a vinylidene fluoride (VDF) polymer [polymer (A)] comprising repeat units derived from a vinylidene fluoride (VDF) monomer, said polymer (A) being (i) Contains more than 85.0 mol % of repeat units derived from VDF, based on the total number of repeat units of polymer (A); (ii) having an iodine-containing chain end in an amount of 0.1 to 5 mmol / kg; (iii) a weight average molecular weight (M) of at least 500 kilodaltons, as measured by gel permeation chromatography (GPC) using N,N-dimethylacetamide (DMA) as the solvent, relative to monodisperse polystyrene standards; w ) According to ASTM D3835, 100 sec -1 The melt viscosity (MV) in kilopoises and M in kilodaltons are determined at a shear rate of 1000 MPa and a temperature of 230°C. w The relationship between is the following inequality: 0.025×M w (kilodalton) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodaltons)+10 and said particles of polymer (A) have an average primary particle size of less than 1 μm.
[0075] All the characteristics stated above in relation to the dispersion (D) and the polymer (A) apply mutatis mutandis to the powder (P).
[0076] The powder (P) may be obtained from the dispersion (D) by known techniques as detailed above. In particular, the powder (P) may be obtained by solidification, for example by shear or temperature induced solidification, or by spray drying or other drying or liquid / solid separation.
[0077] Yet another object of the invention is a polymer (A) having the characteristics detailed above.
[0078] The aqueous electrode-forming composition can be obtained by adding and dispersing the powdered electrode material (active material for a battery or electric double layer capacitor) detailed above, and optional additives, such as a conductivity-imparting additive and / or a viscosity modifier, in the dispersion (D).
[0079] The solvent-based electrode-forming composition may be obtained by solubilizing the powder (P) or polymer (A) detailed above in a polar organic solvent to obtain a binder solution, and by adding and dispersing the powdered electrode material detailed above, and any additives such as the conductivity-imparting additive and / or viscosity modifier detailed above, in said solution.
[0080] Therefore, other objects of the present invention are as follows: - an aqueous electrode-forming composition comprising the dispersion (D) detailed above, a powdered electrode material, and optionally a conductivity-imparting additive and / or a viscosity modifier; and / or - a solvent-based electrode-forming composition comprising the polymer (A) detailed above, a polar organic solvent, a powdered electrode material, and optionally a conductivity-imparting additive and / or a viscosity modifier.
[0081] The polar organic solvent contained in the solvent-based electrode-forming composition and / or used specifically to dissolve the polymer (A) to provide the binder solution according to the present invention may preferably be one or more of the following: N-methyl-2-pyrrolidone, dimethylformamide, N,N-dimethylacetamide, N,N-dimethylsulfoxide, hexamethylphosphamide, dioxane, tetrahydrofuran, tetramethylurea, triethylphosphate, and trimethylphosphate. Since the polymer (A) used in the present invention has a much higher degree of polymerization than the conventional ones, it is more preferable to use a nitrogen-containing organic solvent having a higher dissolving power, for example, N-methyl-2-pyrrolidone, dimethylformamide, or N,N-dimethylacetamide among the above-mentioned organic solvents. These organic solvents may be used alone or in a mixture of two or more.
[0082] To obtain the binder solution of the polymer (A) described above, it is preferable to dissolve 0.1 to 15 parts by weight, particularly 1 to 10 parts by weight, of the polymer (A) in 100 parts by weight of such an organic solvent. If it is less than 0.1 parts by weight, the polymer will occupy too small a proportion in the solution and therefore will tend not to be able to demonstrate its ability to bind the powdered electrode material. If it is more than 15 parts by weight, an abnormally high viscosity of the solution will be obtained, making it difficult to prepare the electrode-forming composition.
[0083] To prepare a polymer (A) binder solution, it is preferable to dissolve the polymer (A) in an organic solvent at a temperature of 25 to 200° C., more preferably 40 to 160° C., and even more preferably 50 to 150° C. If the temperature is less than 25° C., dissolution takes a long time and uniform dissolution becomes difficult.
[0084] Among the viscosity modifiers, thickeners may be added to prevent or slow down the settling of the powdered electrode material from the aqueous or solvent-based electrode-forming composition of the present invention. Those skilled in the art will select the most appropriate thickener depending on the nature of the composition in question. Non-limiting examples of suitable thickeners include organic thickeners such as partially neutralized poly(acrylic acid) or poly(methacrylic acid), carboxylated alkyl cellulose (such as carboxylated methyl cellulose), and inorganic thickeners such as natural clays (such as montmorillonite and bentonite), artificial clays (such as laponite), and others (such as silica and talc), among others.
[0085] When making a positive electrode for a lithium ion battery, the active material may be selected from the group consisting of: Complex metal chalcogenides represented by the general formula LiMY2 (wherein M represents one or more transition metals, such as Co, Ni, Fe, Mn, Cr, and V; Y represents a chalcogen, such as O and S); -Nominal composition formula AB(XO4) f E 1-fThe lithiated or partially lithiated transition metal oxyanion - based electrode material (wherein A is lithium, which may be partially substituted by another alkali metal corresponding to less than 20% of the A metal, B is a main redox transition metal with a +2 oxidation level selected from Fe, Mn, Ni, or a mixture thereof, which may be partially substituted by one or more additional metals with oxidation levels from +1 to +5, represents less than 35% of the +2 main redox metal including 0, XO4 is any oxyanion (where X is any of P, S, V, Si, Nb, Mo, or a combination thereof), E is a fluoride, hydroxide, or chloride anion, and f is the mole fraction of the XO4 oxyanion, usually included between 0.75 and 1).
[0086] Preferred examples thereof may include the following. Li3FePO4, LiCoO2, LiNiO2, LiMnO2LiNi x Co 1-x O2(0 < x < 1), Li x Co 1-y Al y O2(0 < x < 1, 0 < y < 1) and spinel - structured LiMn2O 4; etc. may be included, but a wider range of chalcogenides may be considered, which includes chalcogenides represented by the following formula: Li x Mn 1-y M’ y A2(1) Li x Mn 1-y M’ y O 2-z Z z (2) Li x Mn2O 4-z A z (3) Li x Mn 2-y M’ y A4(4) Li x M 1-y M’’ y A2(5) Li x MO 2-z A z (6) Li x Ni 1-y Co y O 2-z A z (7) Li x Ni 1-y-z Co y M'' z A a (8) Li x Ni 1-y-z Co y M'' z O 2-a Z a (9) Li x Ni 1-y-z Mn y M' z A a (10) Li x Ni 1-y-z Mn y M' z O 2-a Z a (11) (In the formula, -0.95≦x≦1.1, 0≦y≦0.5, 0≦z≦0.5, 0≦a≦2; M is Ni or Co, M' is one or more elements selected from the group consisting of Al, Ni, Co, Cr, Fe, Mg, Sr, V, Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th and Pa, M'' is one or more elements selected from the group consisting of Al, Cr, Mn, Fe, Mg, Sr, V, Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ac, Th and Pa, A is selected from the group consisting of O, F, S and P, and Z is selected from the group consisting of F, S and P).
[0087] Among the composite metal chalcogenides, it is preferable to use lithium-based composite metal oxides represented by the general formula LiMO2 (wherein M is the same as above). Preferable examples thereof include the following: LiCoO2, LiNiO2, LiNi xCo 1-x O2(0 < x < 1), and spinel-structured LiMn2O4 can be mentioned.
[0088] When manufacturing a cathode for a lithium battery, the active material can be selected from the group consisting of: - Carbonaceous materials (such as graphite carbon) into which lithium can be inserted, which are usually present in the form of powders, flakes, fibers, or spheres (such as mesocarbon microbeads) that host lithium; - Lithium metal; - Lithium alloy compositions, especially those described in U.S. Patent No. 6,203,944 (3M INNOVATIVE PROPERTIES CO.) on March 20, 2001 and / or International Publication No. 00 / 03444 Pamphlet (MINNESOTA MINING AND MANUFACTURING CO.) on 10 / 06 / 2005; - Lithium titanate generally represented by the formula Li4Ti5O 12 These compounds are generally considered "zero-strain" insertion materials that have a low level of physical expansion when accepting mobile ions, i.e., Li + Lithium titanate; - Lithium-silicon alloys, especially lithium silicide generally known as high Li / Si ratio lithium silicide, especially lithium silicide of the formula Li 4.4 Si; - Lithium-germanium alloys containing a crystalline phase of the formula Li 4.4 Ge.
[0089] In these embodiments, the active material may preferably include carbonaceous substances such as graphite, activated carbon, or carbonaceous substances obtained by carbonization of phenolic resins, pitches, etc. The carbonaceous substance may preferably be used in the form of particles having an average diameter of about 0.5 to 100 μm.
[0090] In particular, when using active materials such as LiCoO2 that exhibit limited electrical conductivity, conductivity-imparting additives may be added to improve the electrical conductivity of the resulting composite electrode layer formed by application and drying of the electrode-forming composition of the present invention. Examples of these may include carbonaceous materials such as carbon black, graphite fine powder and fiber, and metal fine powders and fibers such as nickel and aluminum.
[0091] The active material for the electric double layer capacitor preferably has an average particle (or fiber) diameter of 0.05 to 100 μm and a mean particle diameter of 100 to 3000 μm. 2 / g, i.e., having a relatively small particle (or fiber) diameter and a relatively large specific surface area compared to that of the active material for the battery, may include fine particles or fibers, such as activated carbon, activated carbon fibers, silica or alumina particles.
[0092] A preferred electrode-forming composition (aqueous or solvent-based) for the anode is (a) polymer (A) in an amount of 1 to 10% by weight, preferably 2 to 9% by weight, more preferably about 3% by weight, based on the total weight of (a)+(b)+(c); (b) carbon black as a conductivity-imparting additive in an amount of 2 to 10% by weight, preferably 4 to 6% by weight, and more preferably about 5% by weight, based on the total weight of (a)+(b)+(c); (c) a powdered electrode material, preferably a metal chalcogenide composite represented by the general formula LiMY2 detailed above, in an amount of 80-97% by weight, preferably 85-94% by weight, more preferably about 92% by weight Includes.
[0093] An aqueous coating composition suitable for coating separators can be obtained by adding and dispersing the non-electroactive inorganic fillers and optional additives detailed above in the dispersion (D).
[0094] A further object of the present invention is therefore an aqueous coating composition [composition (AC)] comprising the dispersion (D) detailed above, at least one non-electroactive inorganic filler, and optionally one or more additional additives.
[0095] The term "non-electroactive inorganic filler" is intended herein to mean an electrically non-conductive inorganic filler suitable for the manufacture of electrically insulating separators for electrochemical cells.
[0096] The non-electroactive inorganic filler in the separator according to the present invention typically has a molecular weight of at least 0.1× as measured at 20° C. according to ASTM D257. 10 Ω (ohm) cm, preferably at least 0.1×10 12 It has an electrical resistivity (p) of Ωcm. Non-limiting examples of suitable non-electroactive inorganic fillers include natural and synthetic silica, zeolites, alumina, titania, metal carbonates, zirconia, silicon phosphates and silicates, among others. Typically, the non-electroactive inorganic fillers are in the form of particles having an average size, measured according to ISO 13321, of 0.01 μm to 50 μm.
[0097] Optional additives in composition (AC) include, inter alia, the viscosity modifiers, antifoam agents, non-fluorinated surfactants, etc. detailed above.
[0098] Among the non-fluorinated surfactants, mention may be made in particular of non-ionic emulsifiers such as alkoxylated alcohols, e.g. ethoxylated alcohols, propoxylated alcohols, mixed ethoxylated / propoxylated alcohols, and anionic surfactants, including in particular fatty acid salts, alkyl sulfonates (e.g. sodium dodecyl sulfate), alkylaryl sulfonates, arylalkyl sulfonates, and the like.
[0099] Composition (AC) can be obtained from dispersion (D), for example, by (i) preparing dispersion (D) with the optional additives detailed above, (ii) concentrating dispersion (D) through standard techniques such as ultrafiltration, atomization, among others, (iii) using dispersion (D) as obtained from emulsion polymerization, (iv) diluting dispersion (D) with water, or through a combination of the above mentioned techniques.
[0100] Generally, the composition (AC) comprises (i) the dispersion (D) detailed above in an amount of 5 to 25% by weight; (ii) at least one non-electroactive inorganic filler in an amount of 70-95 wt. %; (iii) one or more additional additives in an amount of 0 to 5% by weight; Mix the Optionally, water is added to adjust the solid content in the range of 30 to 80% by weight, preferably 40 to 60% by weight.
[0101] The solids content of composition (AC) is understood to be the accumulation of all non-volatile components thereof, including inter alia the polymer (A) and the non-electroactive inorganic fillers.
[0102] Yet another object of the present invention is to provide a method for making a composite separator particularly suitable for use in an electrochemical cell, comprising the steps of: (i) providing a porous substrate; (ii) providing an aqueous coating composition comprising the dispersion (D) as detailed above, at least one non-electroactive inorganic filler, and optionally one or more additional additives, i.e. composition (AC) as detailed above; (iii) applying said composition (AC) onto at least one surface of said porous substrate to provide a coating composition layer; (iv) drying the coating composition layer at a temperature of at least 60° C. to provide the composite separator; The method includes:
[0103] The term "separator" is intended herein to mean a porous polymeric material that electrically and physically separates electrodes of opposite polarity in an electrochemical cell and is permeable to ions flowing between them.
[0104] The term "electrochemical cell" is intended herein to mean an electrochemical cell comprising a positive electrode, a negative electrode and a liquid electrolyte, with a single or multi-layer separator attached to at least one surface of one of the electrodes.
[0105] Non-limiting examples of electrochemical cells include batteries, preferably secondary batteries, and electric double layer capacitors, among others.
[0106] For purposes of the present invention, "secondary battery" is intended to mean a rechargeable battery. Non-limiting examples of secondary batteries include, inter alia, alkaline or alkaline earth secondary batteries.
[0107] The composite separator resulting from the process of the present invention is advantageously an electrically insulating composite separator suitable for use in electrochemical cells.
[0108] In step (iii) of the method of the present invention, the composition (AC) is typically applied onto at least one surface of the porous substrate by a technique selected from casting, spray coating, roll coating, doctor blading, slot die coating, gravure coating, inkjet printing, spin coating and screen printing, brush, squeegee, foam applicator, curtain coating, vacuum coating.
[0109] Non-limiting examples of suitable porous substrates include porous membranes made from inorganic, organic and naturally occurring materials, particularly non-woven fibers (cotton, polyamide, polyester, glass), polymers (polyethylene, polypropylene, poly(tetrafluoroethylene), poly(vinyl chloride) and certain fibrous naturally occurring substances (e.g., asbestos), among others.
[0110] Advantageous results have been obtained when the porous support is a polyolefin porous support, such as a polyethylene or propylene porous support.
[0111] In step (iv) of the method of the present invention, the coating composition layer is dried at a temperature preferably comprised between 60°C and 200°C, preferably between 70°C and 180°C.
[0112] Yet another object of the present invention is a process for the preparation of a membrane comprising the use of the powder (P) or the polymer (A) as detailed above.
[0113] The term "membrane" is used herein in its ordinary sense, i.e., it refers to a discrete (usually thin) interface that moderates the permeation of chemical species in contact with the membrane. This interface may be molecularly uniform (i.e., completely uniform in structure (dense membrane)) or may be chemically or physically heterogeneous, for example, containing voids, holes or pores of finite dimensions (porous membrane).
[0114] Porous membranes are generally characterized by their average pore diameter and porosity, ie, the percentage of the entire membrane that is porous.
[0115] Membranes with a uniform structure throughout their thickness are generally known as symmetric membranes, which can be either dense or porous; membranes with pores that are not uniformly distributed throughout their thickness are generally known as asymmetric membranes. Asymmetric membranes are characterized by a thin selective layer (0.1-1 μm thick) and a thicker, highly porous layer (100-200 μm thick) that acts as a support and has little effect on the separation properties of the membrane.
[0116] Membranes may be in the form of flat sheets or in tubular form. Tubular membranes are classified based on their dimensions in: tubular membranes with a diameter greater than 3 mm; capillary membranes with a diameter comprised between 0.5 mm and 3 mm; and hollow fibers with a diameter less than 0.5 mm. Capillary membranes are often also called hollow fibers.
[0117] Hollow fibers are particularly advantageous in applications where a compact module with large surface area is required, whereas flat sheet membranes are generally preferred where high flux is required.
[0118] Depending on the application, the membrane may be supported to improve its mechanical resistance. The support material is generally chosen to have minimal effect on the selectivity of the membrane.
[0119] The support material may be any of a non-woven material, fiberglass and / or polymeric materials such as polypropylene, polyethylene, polyethylene terephthalate.
[0120] The method for producing said membrane advantageously comprises the following steps: (i) Below: a powder (P) and / or a polymer (A), optionally at least one pore-forming agent [reagent (P)], - Polar organic solvents The solution [solution (S M )]; (ii) The solution (S M) into a film; and (iii) immersing the film in a non-solvent bath Includes.
[0121] The polar organic solvent used in the above method has the same characteristics as described above in connection with the solvent-based electrode-forming composition; preferably, it can be one or more of N-methyl-2-pyrrolidone, dimethylformamide, N,N-dimethylacetamide, N,N-dimethylsulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethylphosphorus phosphate, and trimethylphosphate, and more preferably, it can be one or more of N-methyl-2-pyrrolidone, dimethylformamide, and N,N-dimethylacetamide.
[0122] Pore-forming agents are generally selected from among compounds that have solubility in polar organic solvents and non-solvent baths such that they can be at least partially removed from the membrane being formed, resulting in porosity.
[0123] It is generally understood that inorganic compounds such as lithium chloride can be used, as well as monomeric organic compounds including maleic anhydride, although polymeric pore formers are generally preferred.
[0124] In particular, the polymeric pore former is preferably selected from the group consisting of poly(alkylene oxide) and its derivatives (POA), and polyvinylpyrrolidone (PVP).
[0125] Poly(alkylene oxide)s (PAOs) are polymers derived from polymerizing alkylene oxides, including ethylene oxide, propylene oxide, and mixtures thereof.
[0126] Derivatives of the PAOs can be obtained by reacting their hydroxyl end groups with suitable compounds to produce, in particular, ether groups, especially alkyl ethers, ester groups, such as acetates, and the like.
[0127] Nonetheless, hydroxyl end group PAOs are commonly used.
[0128] Among the PAOs, polyethylene oxide (PEO or PEG) polymers are particularly preferred.
[0129] Polyvinylpyrrolidone (PVP) is generally a homopolymer, although copolymers of vinylpyrrolidone with other monomers can also be advantageously used. Said monomers are generally selected from the group consisting of N-vinylcaprolactam, maleic anhydride, methyl methacrylate, styrene, vinyl acetate, acrylic acid, dimethylaminoethyl methacrylate. Nevertheless, PVP homopolymers are generally utilized.
[0130] The molecular weight of PVP is not particularly limited. Nevertheless, the solution (S M It is understood that a relatively high molecular weight of PVP is more preferable for processing the PVP into a membrane. Thus, the K value of PVP, which is generally recognized as an appropriate measure of its molecular weight, is generally at least 10.
[0131] When used, the amount of reagent (P) is generally comprised between 0.1 and 5% by weight, preferably between 0.5 and 3.5% by weight.
[0132] Solution (S M The solution (S) can be prepared in step (i) in any conventional manner. M ) is advantageously prepared at a temperature of at least 25° C., preferably at least 30° C., more preferably at least 40° C., even more preferably at least 50° C. M ) is advantageously prepared at a temperature below 180° C., preferably below 170° C., more preferably below 160° C., even more preferably below 150° C. Higher temperatures are of course also possible for the solution (S M ) can be used for preparation step (i), but they are not preferred from a practical and / or economic point of view.
[0133] Solution (S M The overall concentration of polymer (A) in the solution (S) should be at least 10% by weight, preferably at least 12% by weight, based on the total weight of the solution. Typically, the concentration of polymer (A) in the solution (S) is at least 10% by weight, preferably at least 12% by weight. M %, preferably does not exceed 40% by weight, and more preferably does not exceed 30% by weight, based on the total weight of the components (a) and (b).
[0134] Solution (S M The mixing time required to obtain a solution (S) depends on the dissolution rates of the ingredients, the temperature, the efficiency of the mixing equipment, and the solution being prepared (S M ) and the like. Advantageously, due to the unique microstructure of the polymer (A), the solution (S M ) but similar M w It has been observed that the resulting suspension-polymerized VDF polymer advantageously has a lower liquid viscosity than that of a corresponding solution containing the suspension-polymerized VDF polymer, which is an interesting advantage with respect to processability.
[0135] Any suitable mixing device may be used. Preferably, the mixing device is adapted to mix the solution (S M The mixing of the polymer and the solvent may conveniently be carried out in a closed vessel, optionally kept under an inert atmosphere. The inert atmosphere, more precisely a nitrogen atmosphere, is selected so as to reduce the amount of air trapped in the PVP-containing solution (S M It has been found to be particularly advantageous for the preparation of
[0136] In step (ii), the solution (S M ) is processed into film.
[0137] The term "film" is used herein to refer to a solution (S M The solution obtained after treatment of M ) Depending on the final form of the membrane, the film may be either flat, if a flat membrane is required, or tubular in shape, if tubular or hollow fiber membranes are to be obtained.
[0138] The conventional technology is a solution (S M ) can be used to process the film, with casting techniques being preferred.
[0139] Different casting techniques are used depending on the final form of the membrane to be produced: If the final product is a flat membrane, the polymer solution is cast using a casting knife or drawdown bar as a film onto a flat support, typically a plate, belt, or fabric, or as another microporous support membrane.
[0140] Thus, in its first embodiment, the method of the present invention comprises the steps of: M ) onto a support to form a flat film.
[0141] Hollow fibres and capillary membranes can be obtained by the so-called wet spinning method. In such a method, a solution (S M A solution (S) is passed through a tubular nozzle that includes a first outer capillary for the passage of the solution (S) and a second inner capillary for a supporting fluid, commonly referred to as a "lumen." M ) is pumped through the lumen. M ) and maintains the holes of the hollow fiber or capillary precursor open. The lumen can be gaseous or preferably liquid at the conditions of fiber spinning. The choice of the lumen and its temperature depends on the properties required for the final membrane, since they can have a significant effect on the size and distribution of the pores in the membrane. Generally, the lumen is not a strong non-solvent for the polymer (A), or alternatively, the lumen contains a solvent or a weak solvent for the polymer (A). The lumen is generally miscible with the non-solvent for the polymer (A) and with the polar organic solvent.
[0142] At the exit of the spinneret, after a short residence time in air or in a controlled environment, the hollow fiber or capillary precursor is immersed in a non-solvent bath where the polymer (A) precipitates to form the hollow fiber or capillary membrane.
[0143] Thus, in its second embodiment, the method of the invention comprises a step (ii) of casting the polymer solution around a supporting fluid into a tubular film.
[0144] Casting of the polymer solution is generally done through a spinneret. The supporting fluid forms the holes of the final hollow fiber or capillary membrane. If the supporting fluid is a liquid, immersion of the fiber precursor in a non-solvent bath also advantageously removes the supporting fluid from the interior of the fiber.
[0145] Because of their larger diameter, tubular membranes are manufactured using methods that differ from those used to manufacture hollow fiber membranes.
[0146] In its third embodiment, the method of the present invention comprises a step (ii) of casting the polymer solution onto a supporting tubular material into a tubular film.
[0147] Solution (S M After the above detailed process is completed to obtain a film in any form, the film is immersed in a non-solvent bath in step (iii). This step is usually carried out using a solution (S M ) so that the precipitated polymer (A) advantageously forms the final membrane structure.
[0148] As used herein, the term "non-solvent" is intended to mean a substance in which a given component of a solution or mixture cannot be dissolved.
[0149] Suitable non-solvents for polymer (A) are water and aliphatic alcohols, preferably aliphatic alcohols having a short chain (e.g., 1 to 6 carbon atoms), more preferably methanol, ethanol, and isopropanol. Blends of the above preferred non-solvents can be used, i.e. blends comprising water and one or more aliphatic alcohols. Preferably, the non-solvent of the non-solvent bath is water, - Fatty alcohols as defined above and their mixtures Furthermore, the non-solvent bath may contain, in addition to the non-solvent (for example, in addition to water, the aliphatic alcohols detailed above or a mixture of water and aliphatic alcohols), a small amount (typically up to 40% by weight, generally 25-40% by weight, based on the total weight of the non-solvent bath) of a solvent for the polymer (A). The use of a solvent / non-solvent mixture advantageously makes it possible to control the porosity of the membrane. The non-solvent is usually a solvent (S M The non-solvent is selected from those that are miscible with the polar organic solvent used in the preparation of the compound (III). Preferably, the non-solvent in the process of the present invention is water. Water is the least expensive non-solvent and can be used in large quantities.
[0150] If used, the pore-forming agent (P) is generally at least partially, if not completely, removed from the membrane in the non-solvent bath in step (iii).
[0151] Once removed from the deposition bath, the membrane may be subjected to further treatment (e.g., rinsing) and, as a final step, the membrane is typically dried.
[0152] The present invention further relates to a membrane obtainable by the process as described above.
[0153] The membrane obtained from the method of the present invention is preferably a porous membrane. Typically the membrane has an asymmetric structure. The porosity of the membrane may be in the range of 3 to 90%, preferably 5 to 80%.
[0154] The pores may have an average diameter of at least 0.001 μm, at least 0.005 μm, at least 0.01 μm, at least 0.1 μm, at least 1 μm, at least 10 μm and at most 50 μm.
[0155] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements of this application to the extent that a term may be unclear, this statement shall control.
[0156] The present invention will now be described in more detail with reference to the following examples, which are provided merely for the purpose of illustrating the invention and are not intended to limit the scope of the invention.
[0157] End group determination To determine the end groups, the technique described in PIANCA, Maurizio et al., End groups in fluoropolymers. Journal of Fluorine Chemistry. 1999, vol. 95, p. 71-84 is used. 1 H-NMR technique was used. For this purpose, about 20 mg of polymer was dissolved in 0.7 mL of hexadeuteroacetone. 1 The H-NMR spectrum elucidated, inter alia, a triplet at 3.78 ppm with a J-coupling FH equal to 14 Hz associated with the -CH2-OH end group.
[0158] Determination of total average monomer (MA) content The total average monomer (MA) content in vinylidene fluoride (VDF) polymers was determined by acid-base titration method.
[0159] A 1.0 g sample of the polymer was dissolved in acetone at a temperature of 70° C. Then, water (5 mL) was added dropwise under strong stirring to avoid solidification of the polymer. Then, titration with aqueous NaOH having a concentration of 0.01 N was carried out until the acidity was completely neutralized with a neutrality transition at about −170 mV.
[0160] Determination of melt viscosity To verify the molecular weight improvement, the melt viscosity (according to ASTM D3835) was measured. The test was carried out in a capillary rheometer Rheograph 2003 at 230° C. in one geometry (L / D=20) with a die diameter of 1 mm. The MV measurement was performed at 100 sec -1 The shear rate was 100 rpm.
[0161] Determination of weight average molecular weight The molecular weight was determined by GPC. Sample preparation: Dissolution of the powder obtained by coagulation of 0.25 wt% / volume + LiBr 0.01N in DMA was performed at 45°C under stirring for 2 hours and further centrifugation was performed at 20000 rpm for 60 minutes at room temperature using a Sorvall RC-6 Plus centrifuge (rotor model: F21S-8X50Y). The supernatant of each sample was analyzed using the equipment and conditions detailed below. Mobile phase: DMA Flow rate: 1mL / min Temperature: 45℃ Injection system: Waters 717plus Autosampler Injection volume: 200 μL. Pump: Waters Isocratic Pump model 515 Column: Four Water Styragel HT (300x7.5) mm, 10μm particle size: Styragel HT-6, HT-5, HT-4, HT-3 guarded columns Detector: Waters refractive index model 2414 Software for data collection and processing: Waters Empower
[0162] Gel content determination A sample of the latex obtained was dried and the latex was frozen by low temperature coagulation technique; a weighed amount of the powder so obtained was contacted with N,N-dimethylacetamide (DMA) containing LiBr at a concentration of 0.01N in a weight ratio of 1:375 at a temperature of 45°C for 4 hours. The mixture so obtained was subjected to centrifugation at 20000 rpm for 3600 seconds and the liquid phase was separated from the precipitated residue. The gel content was determined by weighing the residue after drying at a temperature of 150°C for 48 hours and dividing it by the total weight of the coagulated powder specimen.
[0163] Example 1 - Preparation of Water-Based VDF-HFP-AA Polymer Latex - Polymer A1 13.5 liters of deionized water were introduced into a 21 liter horizontal reactor autoclave equipped with baffles and a stirrer operating at 50 rpm. The temperature was brought to 80° C., and a pressure of more than 35 bar was kept constant throughout the entire trial by adding 75 ml of a 29.4 g / l aqueous potassium iodide (KI) solution and feeding the VDF / HFP gaseous mixture monomers in a molar ratio of 99:1, respectively. 250 ml of a 100 g / l aqueous ammonium persulfate (APS) solution were added over 20 minutes (1 L / h), after which the ammonium persulfate (APS) solution was added continuously at a flow rate of 70 ml / h for the entire duration of the run. In addition, 50 ml of acrylic acid (AA) solution (50 g / l aqueous acrylic acid solution) were fed every 250 g of monomer consumed.
[0164] When 4500 g of the mixture had been fed, the feed of the mixture was interrupted, then the pressure was reduced to 12 bar, while the reaction temperature was kept constant. The final reaction time was 270 minutes. The reactor was cooled to room temperature and the latex was recovered. The VDF-HFP-AA polymer thus obtained contained 98.6 mol % VDF, about 1.0 mol % HFP and 0.4 mol % acrylic acid (AA) monomer. The final ratio (KI) / APS was 0.054 mol / mol. The aqueous latex thus obtained had a solids content (coagulated) of 24.8 wt %.
[0165] The VDF-HFP-AA polymer, when dispersed in an aqueous latex in the form of particles having an average primary particle size of 243 nm, measured according to ISO 13321, has a melting point of 154.7°C (measured according to ASTM D3418), a MV (230°C / 100 sec) of 41.5 kpoise, and a viscosity of 1.0 MPa (measured according to ASTM D3418). -1 ), M of 925 kilodaltons w , a gel content of less than 3% and the following end group composition: -CF2H: 27 mmol / kg; -CF2-CH3: 22 mmol / kg; -CH2OH: 10 mmol / kg; -CH2I: 2 mmol / kg.
[0166] Example 2 - Preparation of Water-Based VDF-HFP-AA Polymer Latex - Polymer A2 13.5 liters of deionized water were introduced into a 21 liter horizontal reactor autoclave equipped with baffles and a stirrer operating at 50 rpm. The temperature was brought to 80° C., and 1.45 ml of pure diiodomethane (CH2I2) was added, and the pressure was kept constant throughout the entire trial at more than 35 bar by feeding the VDF / HFP gaseous mixture monomers in a molar ratio of 99:1, respectively. 250 ml of a 100 g / l aqueous solution of ammonium persulfate (APS) was added over 20 minutes (1 L / h), after which the ammonium persulfate (APS) solution was added continuously at a flow rate of 70 ml / h for the entire duration of the run. In addition, 50 ml of acrylic acid (AA) solution (50 g / l aqueous solution of acrylic acid) was fed every 250 g of monomer consumed.
[0167] When 4500 g of the mixture had been fed, the feed of the mixture was interrupted, then the pressure was reduced to 12 bar while keeping the reaction temperature constant. The final reaction time was 200 minutes. The reactor was cooled to room temperature and the latex was recovered. The VDF-HFP-AA polymer so obtained contained 98.8 mol % VDF, about 1.0 mol % HFP and 0.2 mol % acrylic acid (AA) monomer. The final ratio CH2I2 / APS was 0.038 mol / mol.
[0168] The aqueous latex so obtained had a solids content of 25.1% by weight. The VDF-HFP-AA polymer, when dispersed in the aqueous latex in the form of particles having an average primary particle size of 217 nm, measured according to ISO 13321, had a melting point of 155.0° C. (measured according to ASTM D3418), a MV (230° C. / 100 sec ) of 31.4 kpoise, and a viscosity of 1.0 MPa (measured according to ASTM D3418). -1 ), M of 789 kilodaltons w , a gel content of less than 3% and the following end group composition: -CF2H: 28 mmol / kg; -CF2-CH3: 19 mmol / kg; -CH2OH: 13 mmol / kg; -CH2I: 4 mmol / kg.
[0169] Example 3 - Preparation of Water-Based VDF-HFP-AA Polymer Latex - Polymer A3 13.5 liters of deionized water were introduced into a 21 liter horizontal reactor autoclave equipped with baffles and a stirrer operating at 50 rpm. The temperature was brought to 80° C., and 5.5 ml of a 0.33 ml / ml solution of 1,4-diiodooctafluorobutane in GALDEN® D02 was added, and the pressure was kept constant at more than 35 bar throughout the entire trial by feeding the VDF / HFP gaseous mixture monomers in a molar ratio of 99:1, respectively. 120 ml of a 100 g / l aqueous solution of ammonium persulfate (APS) were added over 10 minutes (1 L / h), after which the ammonium persulfate (APS) solution was added continuously at a flow rate of 60 ml / h for the entire duration of the run. In addition, 50 ml of acrylic acid (AA) solution (50 g / l aqueous solution of acrylic acid) was fed every 250 g of monomer consumed.
[0170] When 4500 g of the mixture had been fed, the feed of the mixture was interrupted and then the pressure was reduced to 12 bar while keeping the reaction temperature constant. The final reaction time was 333 minutes. The reactor was cooled to room temperature and the latex was recovered. The VDF-HFP-AA polymer thus obtained contained 98.7 mol % VDF, about 0.9 mol % HFP and 0.4 mol % acrylic acid (AA) monomer. The final ratio (C4F8I2) / APS was 0.05 mol / mol. The aqueous latex thus obtained had a solids content of 24.6% by weight. The VDF-HFP-AA polymer, when dispersed in the aqueous latex in the form of particles having an average primary particle size of 208 nm, measured according to ISO 13321, had a melting point of 153.6° C. (measured according to ASTM D3418), a MV (230° C. / 100 sec) of 47.9 kpoise. -1 ), Mw of 990 kilodaltons, gel content of less than 3%, and the following end group composition: -CF2H: 27 mmol / kg; -CF2-CH3: 19 mmol / kg; -CH2OH: 10 mmol / kg; -CH2I: 4 mmol / kg.
[0171] Comparative Example 1 - Preparation of Water-Based VDF-AA Polymer Latex - Polymer C1 13.5 liters of deionized water were introduced into a 21 liter horizontal reactor autoclave equipped with baffles and a stirrer operating at 50 rpm. The temperature was brought to 80° C. and the pressure was kept constant at more than 35 bar throughout the entire trial by feeding a VDF / HFP gaseous mixture monomer in a molar ratio of 99:1, respectively. 250 ml of a 100 g / l aqueous solution of ammonium persulfate (APS) was added over 20 minutes (1 L / h), after which the ammonium persulfate (APS) solution was added continuously at a flow rate of 60 ml / h for the entire duration of the run. In addition, 50 ml of acrylic acid (AA) solution (50 g / l aqueous solution of acrylic acid) was fed for every 250 g of monomer consumed.
[0172] When 4500 g of the mixture had been fed, the feed of the mixture was interrupted, then the pressure was reduced to 12 bar while the reaction temperature was kept constant. The final reaction time was 183 minutes. The reactor was cooled to room temperature and the latex was recovered. The VDF-HFP-AA polymer thus obtained contained 98.6 mol % VDF, about 1.0 mol % HFP and 0.4 mol % acrylic acid (AA) monomer.
[0173] The aqueous latex so obtained had a solids content of 24.9% by weight. The VDF-HFP-AA polymer, when dispersed in the aqueous latex in the form of particles having an average primary particle size of 221 nm, measured according to ISO 13321, had a melting point of 153° C. (measured according to ASTM D3418), a MV (230° C. / 100 sec ) of 60 kpoise, and a viscosity of 1.0 MPa (measured according to ASTM D3418). -1 ), Mw of 470 kilodaltons, gel content of 55% and the following end group composition: -CF2H: 43 mmol / kg; -CF2-CH3: 47 mmol / kg; -CH2OH: 9 mmol / kg. No iodine-containing end groups were found to be present, which is consistent with the fact that no iodine-containing chain transfer agent was used.
[0174] Comparative Example 2 - Preparation of Water-Based VDF-AA Polymer Latex - Polymer C2 13.5 liters of deionized water were introduced into a 21 liter horizontal reactor autoclave equipped with baffles and a stirrer operating at 50 rpm. The temperature was brought to 80° C., and 13.5 ml of a 6.6% volume / volume aqueous solution of ethyl acetate (AcOEt) was added, and the pressure was kept constant at more than 35 bar throughout the entire trial by feeding the VDF / HFP gaseous mixture monomers in a molar ratio of 99:1, respectively. 250 ml of a 100 g / l aqueous solution of ammonium persulfate (APS) were added over 20 minutes (1 L / h), after which the ammonium persulfate (APS) solution was added continuously at a flow rate of 60 ml / h for the entire duration of the run. Furthermore, 50 ml of acrylic acid (AA) solution (50 g / l aqueous solution of acrylic acid) was fed every 250 g of monomer consumed.
[0175] When 4500 g of the mixture had been fed, the feed of the mixture was interrupted, then the pressure was reduced to 12 bar, while the reaction temperature was kept constant. The final reaction time was 211 minutes. The reactor was cooled to room temperature and the latex was recovered. The VDF-HFP-AA polymer so obtained contained 98.7 mol % VDF, about 0.9 mol % HFP and 0.4 mol % acrylic acid (AA) monomer. The final ratio AcOEt / APS was 0.05 mol / mol.
[0176] The aqueous latex so obtained had a solids content of 23.2% by weight. The VDF-HFP-AA polymer, when dispersed in the aqueous latex in the form of particles having an average primary particle size of 330 nm, measured according to ISO 13321, had a melting point of 153.2° C. (measured according to ASTM D3418), a MV (230° C. / 100 sec ) of 49.9 kpoise, and a viscosity of 1.0 MPa (measured according to ASTM D3418). -1 ), M of 596 kilodaltons w , 35% gel content and the following end group composition: -CF2H: 45 mmol / kg; -CF2-CH3: 42 mmol / kg; -CH2OH: 9 mmol / kg. As above, no iodine-containing end groups were found to be present, which is consistent with the fact that no iodine-containing chain transfer agent was used.
[0177] The table below provides an overview of the chain ends detected in the polymers so obtained.
[0178] TIFF0007657716000007.tif103170
[0179] The data provided above fully demonstrates that the use of limited amounts of iodized chain transfer agents makes it possible to achieve high molecular weight latexes with substantially limited overall amount of branch-related chain ends.
[0180] The following table provides an overview of the results obtained when the cold coagulated latex obtained in the above detailed examples is dissolved in DMA for gel content determination as detailed above. Additionally, the coagulated samples were also solubilized in NMP at a weight content of 8% w / w. A qualitative assessment is provided below. When assessed as "good", it represents a clear and homogenous solution without suspended / gelled fractions, perfectly adapted for preparing an electrode-forming composition by addition of electrode active material and / or conductivity promoter, whereas "poor" represents a heterogeneous solution that may require additional separation steps to be suitable for use in preparing an electrode-forming composition.
[0181] TIFF0007657716000008.tif92170
[0182] The data provided above clearly demonstrates that the latices of the present invention, due to their improved linear and limited content of long chain branching, given their higher molecular weight, have improved solubilization behavior and, in particular, provide solutions in organic solvents that are not adversely affected by the presence of insoluble residues, commonly referred to as "gels", thus providing products that are more suitable for use in preparing electrode-forming compositions.
[0183] Figure 1 is a graph showing the relationship between the melt viscosity in kilopoise (MV) measured as above and the weight average molecular weight in kilodaltons (Mw) for the VDF polymers of Examples 1 to 3 and other similar polymers obtained under substantially similar conditions in the presence of an iodine-containing chain transfer agent in an amount such that the molar ratio between the chain transfer agent and the initiator used is maintained below 0.100 mole / mole. These are indicated using the symbol □. The graph is based on the inequality 0.025 x M w (kilodalton) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodaltons) + 10 and 0.030 x M w (kilodalton) + 12 ≤ MV (kilopoise) ≤ 0.045 x M wAlso shown are lines corresponding to the upper and lower boundaries of (kilodaltons)+9. This graph clearly shows the manner in which the inventive VDF-polymers (□) are characterized by a peculiar Mw / MV relationship that clearly distinguishes them (i) from reference emulsion-polymerized VDF-polymers (●) such as the latices of Comparative Examples 1C and 2C above, as well as other emulsion-polymerized latexes obtained by methods different from those described herein, and (ii) from suspension-polymerized VDF-polymers (○) known to have a very linear structure and obtained in granular form (not latex) by suspension polymerization under high VDF pressures, higher than the critical VDF pressure, known to be 4.43 MPa (corresponding to 44.3 bar), and therefore in the presence of liquid VDF in the reaction medium.
[0184] Example 4 - Preparation of Water-Based VDF-AA Polymer Latex - Polymer A4 The procedure described in Example 1 was essentially reproduced, without the use of HFP, to prepare Polymer A4, which has essentially similar end groups as Polymer A1 and has the Mw and MV summarized in Table 3 below.
[0185] TIFF0007657716000009.tif31170
[0186] Porous membrane production N,N-Dimethylacetamide (DMAc), PEG 200 and PVP K10 were purchased from Sigma Aldrich.
[0187] Solutions were prepared by mixing A4 in combination with DMAc and, optionally, pore formers (PVP K10 and PEG 200) in glass vials with magnetic stirring. Dissolution was achieved at temperatures ranging from 25° C. to 80° C. All solutions were homogenous and stable for several weeks with substantial absence of insoluble residue.
[0188] Flat sheet porous membranes were prepared by filming the above solution on a suitable smooth glass support with an automated casting knife. Membrane casting was performed by maintaining the temperature of the dope solution, casting knife, and support at 25° C. to prevent premature precipitation of the polymer. The knife gap was set at 250 μm. After casting, the porous membrane film was immediately immersed in a coagulation bath to induce phase inversion. This coagulation bath consisted of pure deionized water. After coagulation, the membrane was washed several times in pure water over the next few days to remove residual traces of solvent. The membrane was always stored in water.
[0189] The dope compositions used to prepare the membranes are shown in the table below, along with comparative dopes prepared from commercially available SOLEF® PVDF 6020, which has a Mw of about 700 kilodaltons, and from commercially available SOLEF® PVDF 1015, which has a lower Mw.
[0190] Fluid viscosity data was obtained at 30° C. using a Rheometric Scientific RFS III rheometer in a concentric cylinder configuration in the shear rate region and the solution was found to have substantially Newtonian behavior.
[0191] TIFF0007657716000010.tif44170
[0192] The data summarized above amply demonstrates that polymer (A) has a high molecular weight but can provide low viscosity in the dope solutions, thus making them easier to process into membranes.
[0193] Membrane gravimetric porosity and mechanical properties Gravimetric membrane porosity (ε) was measured using IPA (isopropyl alcohol) as the wetting fluid according to the procedure described in Appendix of Desalination, 72 (1989) 249-262. A completely dry membrane specimen was weighed and soaked in isopropyl alcohol (IPA) for 24 hours. After this time, excess liquid was removed with tissue paper and the membrane weight was measured again.
[0194] To determine ε, the following formula was used: TIFF0007657716000011.tif24170 (in the formula, "Wet" is the weight of the wet film, "Dry" is the weight of the dry film, ρ polymer PVDF (1.76g / cm 3 ) and ρ liquid is IPA (0.78g / cm 3 ) was the density
[0195] The mechanical properties were evaluated at room temperature (23 °C) according to the ASTM D 638 standard procedure (Type V, grip distance = 25.4 mm, initial length Lo = 21.5 mm). The speed was 1-50 mm / min. At least five specimens of each membrane were tested immediately after removal from the demineralized water used for storage and after 4 weeks of storage in a NaOH aqueous solution with pH = 12. The results are the average of the individual values obtained.
[0196] TIFF0007657716000012.tif41170
[0197] Membranes made from polymer (A) exhibit improved resistance to alkaline solutions as demonstrated by retention of original mechanical performance, particularly the original strain at break.
Claims
1. An aqueous dispersion [dispersion (D)] comprising particles of a vinylidene fluoride (VDF) polymer [polymer (A)] comprising repeating units derived from a vinylidene fluoride (VDF) monomer, said polymer (A) being (i) comprises more than 85.0 mol % of repeat units derived from VDF, based on the total number of repeat units of polymer (A); (ii) having iodine-containing chain ends in an amount of 0.1 to 5.0 mmol / kg; (iii) a weight average molecular weight (M) of at least 500 kilodaltons and at most 1500 kilodaltons, as measured by GPC using N,N-dimethylacetamide (DMA) as the solvent, relative to monodisperse polystyrene standards; w ) According to ASTM D3835, 100 sec -1 and a temperature of 230° C.; and M w The relationship between is the following inequality: 0.025 x M w (kilodaltons) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodalton) +10 An aqueous dispersion [dispersion (D)] which satisfies the above.
2. The polymer (A) is selected from the group consisting of: repeating units derived from VDF and of the formula: (Wherein, R1 and R2 are equal to or different from each other and independently represent a hydrogen atom or C 1 ~C 3 is a hydrocarbon group, R is hydrogen, and R OH is a hydroxyl group or a C containing at least one hydroxyl group 1 ~C 5 a polymer consisting essentially of repeat units derived from at least one hydrophilic (meth)acrylic monomer (MA) according to - a polymer consisting essentially of repeat units derived from VDF, repeat units derived from HFP and repeat units derived from a hydrophilic (meth)acrylic monomer (MA). The dispersion (D) according to claim 1, selected from the group consisting of:
3. The hydrophilic (meth)acrylic monomer (MA) - Formula: Hydroxyethyl acrylate (HEA), - Formula: 2-Hydroxypropyl acrylate (HPA) - Formula: of acrylic acid (AA) - and mixtures thereof The dispersion (D) according to claim 2, selected from the group consisting of:
4. Dispersion (D) according to any one of claims 1 to 3, wherein polymer (A) comprises at least 0.1 mol % of repeat units derived from said hydrophilic (meth)acrylic monomer (MA) and / or polymer (A) comprises at most 7.5 mol % of repeat units derived from said hydrophilic (meth)acrylic monomer (MA).
5. 5. A process for the preparation of dispersion (D) according to any one of claims 1 to 4, comprising the emulsion polymerization of VDF in an aqueous medium in the presence of an iodine-containing chain transfer agent and an inorganic initiator, the molar ratio between said initiator and said iodine-containing chain transfer agent being less than 0.100 mol / mol.
6. 6. The method of claim 5, wherein the initiator is a persulfate radical initiator selected from the group consisting of sodium persulfate, potassium persulfate and ammonium persulfate, and the amount of the initiator ranges from 0.001% to 20% by weight based on the weight of the aqueous medium.
7. The iodine-containing chain transfer agent is - Formula R H (I) x (In the formula, R H is a fluorine-free alkyl group containing 1 to 8 carbon atoms, and x is an integer from 0 to 2; - Formula R f (I) x (In the formula, R f is a (per)fluoroalkyl or (per)fluorochloroalkyl containing 1 to 8 carbon atoms, and x is an integer from 0 to 2; and - alkali metal or alkaline earth metal iodides, in particular potassium iodide Generally selected from the group consisting of and / or the amount of iodine-containing chain transfer agent is such that a molar ratio between the iodine-containing chain transfer agent and the initiator of at most 0.075 mol / mol and / or at least 0.005 mol / mol is provided.
8. A powder [powder (P)] comprising particles of a vinylidene fluoride (VDF) polymer [polymer (A)] comprising repeating units derived from a vinylidene fluoride (VDF) monomer, said polymer (A) being (i) comprises more than 85.0 mol % of repeat units derived from VDF, based on the total number of repeat units of polymer (A); (ii) having iodine-containing chain ends in an amount of 0.1 to 5.0 mmol / kg; (iii) a weight average molecular weight (M) of at least 500 kilodaltons and at most 1500 kilodaltons, as measured by GPC using N,N-dimethylacetamide (DMA) as the solvent, relative to monodisperse polystyrene standards; w ) According to ASTM D3835, 100 sec -1 and a temperature of 230° C.; and M w The relationship between is the following inequality: 0.025 x M w (kilodaltons) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodalton) +10 Fulfilling A powder [powder (P)], wherein said particles of polymer (A) have a primary particle average diameter of less than 1 μm.
9. A vinylidene fluoride (VDF) polymer [polymer (A)] comprising repeating units derived from a vinylidene fluoride (VDF) monomer, said polymer (A) comprising: (i) comprises more than 85.0 mol % of repeat units derived from VDF, based on the total number of repeat units of polymer (A); (ii) having iodine-containing chain ends in an amount of 0.1 to 5.0 mmol / kg; (iii) a weight average molecular weight (M) of at least 500 kilodaltons and at most 1500 kilodaltons, as measured by GPC using N,N-dimethylacetamide (DMA) as the solvent, relative to monodisperse polystyrene standards; w ) According to ASTM D3835, 100 sec -1 and a temperature of 230° C.; and M w The relationship between is the following inequality: 0.025 x M w (kilodaltons) + 13 ≤ MV (kilopoise) ≤ 0.050 x M w (kilodalton) +10 A vinylidene fluoride (VDF) polymer [polymer (A)] that satisfies the above.
10. 10. A solvent-based electrode-forming composition comprising the polymer (A) of claim 9, at least one polar organic solvent, a powdered electrode material, and optionally a conductivity-imparting additive and / or a viscosity modifier, The solvent-based electrode-forming composition, wherein the polar organic solvent is one or more of N-methyl-2-pyrrolidone, dimethylformamide, N,N-dimethylacetamide, N,N-dimethylsulfoxide, hexamethylphosphonamide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, and trimethyl phosphate.
11. An aqueous electrode-forming composition comprising the dispersion (D) according to any one of claims 1 to 4, a powdered electrode material, and optionally a conductivity-imparting additive and / or a viscosity modifier.
12. 5. An aqueous coating composition [composition (AC)] comprising the dispersion (D) according to any one of claims 1 to 4, at least one non-electroactive inorganic filler, and optionally one or more additional additives.
13. 13. Composition (AC) according to claim 12, wherein said non-electroactive inorganic filler is selected from the group consisting of natural and synthetic silicas, zeolites, aluminas, titania, metal carbonates, zirconia, silicon phosphates and silicates.
14. The composition (AC) (i) the dispersion (D) detailed above in an amount of 5 to 25% by weight; (ii) at least one non-electroactive inorganic filler in an amount of 70 to 95 weight percent; (iii) one or more additional additives in an amount of 0 to 5 wt. %; Mix the Composition (AC) according to any one of claims 12 to 13, optionally obtained by adding water in the range of 30-80% by weight to adjust the solids content.
15. A method for making a composite separator particularly suitable for use in an electrochemical cell comprising the steps of: (i) providing a porous substrate; (ii) providing a composition (AC) as defined in any one of claims 12 to 13; (iii) applying said composition (AC) onto at least one surface of said porous substrate to provide a coating composition layer; (iv) drying the coating composition layer at a temperature of at least 60° C. to provide the composite separator; The method includes:
16. A method for producing a membrane, comprising using a powder (P) according to claim 8 or a polymer (A) according to claim 9, (i) Below: a polymer (A), optionally at least one pore-forming agent [reagent (P)], - Polar organic solvent A solution [solution (S M ) (a) preparing a solution of (ii) The solution (S M ) into a film; and (iii) immersing the film in a non-solvent bath The method includes:
17. A membrane comprising a polymer (A) according to claim 9 or obtainable from the method according to claim 16.